Simultaneous Effect between Financial Reporting Aggressiveness and Tax Reporting Aggressiveness: The Impact on The Earnings Informativeness - Intan Kurnia Suharti; Dianwicaksih Arieftiara (The Indonesian Journal of Accounting Research, 2019)
Abstract: This study aims to analyze the simultaneous effect between Financial Reporting Aggressiveness and Tax Reporting Aggressiveness. Moreover, this study aims to examine the impact of financial reporting aggressiveness (that had been influenced by the level of tax reporting aggressiveness) on the earnings informativeness. In addition, this study also aims to investigate the impact of tax reporting aggressiveness (that had been influenced by the level of financial reporting aggressiveness) on the earnings informativeness. Using TSLS method and sample consists of Indonesian listed manufacture companies for the period 2013 – 2016, this study found that the financial reporting aggressiveness and tax reporting aggressiveness have simultaneous effect. However, this study failed to demonstrates that the simultaneous effect between financial reporting aggressiveness and tax reporting aggressiveness have significant impact on earnings informativeness. There are two contributions expected from this study, first, it provides empirical evidence that financial reporting aggressiveness and tax reporting aggressiveness have simultaneously effect, since this study is the first that investigates this area. Second, this research also the first that focused on analyze the earnings informativeness impact of managers’ activity in financial reporting and tax reporting aggressiveness.